2015
DOI: 10.1126/scisignal.aaa2581
|View full text |Cite
|
Sign up to set email alerts
|

HDL-bound sphingosine 1-phosphate acts as a biased agonist for the endothelial cell receptor S1P 1 to limit vascular inflammation

Abstract: The sphingosine 1-phosphate receptor 1 (S1P1) is abundant in endothelial cells, where it regulates vascular development and microvascular barrier function. In investigating the role of endothelial cell S1P1 in adult mice, we found that the endothelial S1P1 signal was enhanced in regions of the arterial vasculature experiencing inflammation. The abundance of proinflammatory adhesion proteins, such as ICAM-1, was enhanced in mice with endothelial cell–specific deletion of S1pr1 and suppressed in mice with endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
271
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 271 publications
(291 citation statements)
references
References 57 publications
(78 reference statements)
11
271
0
Order By: Relevance
“…Mice were housed in individual ventilated cages in a temperature-controlled facility with a 12-h light/dark cycle at Weill Cornell Medical College. EC-specific S1pr1 knockout mice (S1pr1 flox/flox Cdh5-Cre-ER T2 ; S1pr1 iECKO ) were generated as described (12,13,16,17). Mice were treated with tamoxifen by oral gavage (50 μg/d) for the first 3 d after birth and used for the experiments at the age of 10-16 wk.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were housed in individual ventilated cages in a temperature-controlled facility with a 12-h light/dark cycle at Weill Cornell Medical College. EC-specific S1pr1 knockout mice (S1pr1 flox/flox Cdh5-Cre-ER T2 ; S1pr1 iECKO ) were generated as described (12,13,16,17). Mice were treated with tamoxifen by oral gavage (50 μg/d) for the first 3 d after birth and used for the experiments at the age of 10-16 wk.…”
Section: Methodsmentioning
confidence: 99%
“…Cdh5-Cre-ER T2 ; referred to as S1pr1 iECKO ) (12,(15)(16)(17). Mice were treated with tamoxifen for the first 3 d after birth and allowed to develop into adulthood.…”
Section: Significancementioning
confidence: 99%
“…112,113 Of note, at least some functions of S1P appear to be only exerted if S1P is present on HDL. 107 This is of note because only about 50% of S1P in plasma is transported by HDL. The rest is transported by albumin (about 30%) and apoB-containing lipoproteins.…”
Section: Sphingolipidsmentioning
confidence: 99%
“…It has been recently suggested that S1P bound to ApoM-containing HDL activates endothelial S1PR1 and results in a suppression of inflammatory responses (53). Although the structure of the ApoM protein supports the binding of S1P and HDL-associated S1P is bound specifically to ApoM such that ApoM-containing HDL contain S1P, whereas HDL devoid of ApoM do not (52), Sattler et al (54) have clearly demonstrated that S1P can be loaded in vitro or in vivo onto HDL, which are virtually absent of ApoM, and restore the defective signaling of the HDLs.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the role of lipoprotein ApoM in the transfer of S1P in lipoproteins onto cell S1P receptors remains to be determined. It has been further suggested that apoM-containing HDL engage endothelial S1P1 to form a signaling complex with -arrestin 2 that suppresses nuclear factor B-dependent inflammatory pathways (53). In another recent study, it was shown that HDL from patients with mild coronary artery disease contains 5-fold less S1P concentration than HDL from healthy individuals (54) and that the S1P-deficient HDL is less efficient in activating endothelial molecular pathways.…”
Section: Discussionmentioning
confidence: 99%